1991
DOI: 10.1111/j.1651-2227.1991.tb11832.x
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deficiency in Coeliac Disease Is Mild and It Is Detected and Corrected by Gluten‐free Diet

Abstract: In 54 children with coeliac disease, mild iron deficiency anaemia or evidence of iron deficiency without anaemia were common at the time of diagnosis. Treatment with a gluten-free diet without iron medication eliminated all evidence of iron deficiency and completely normalized laboratory values. Subsequent challenge with gluten resulted in the rapid reappearance of suboptimal iron balance as evidenced by a decrease in serum ferritin concentration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 9 publications
3
9
0
Order By: Relevance
“…It has been reported that about 15-38% of untreated coeliac disease patients suffer from anaemia or nutritional deficiencies [35-37]. Nevertheless, these are usually abolished on a gluten-free diet [35,38], and implementation of specific dietary supplements after the diagnosis is not routinely recommended in current clinical guidelines [39]. Consequently, we believe that in most cases the supplements were not prescribed by a physician but started voluntarily by the patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that about 15-38% of untreated coeliac disease patients suffer from anaemia or nutritional deficiencies [35-37]. Nevertheless, these are usually abolished on a gluten-free diet [35,38], and implementation of specific dietary supplements after the diagnosis is not routinely recommended in current clinical guidelines [39]. Consequently, we believe that in most cases the supplements were not prescribed by a physician but started voluntarily by the patients.…”
Section: Discussionmentioning
confidence: 99%
“…The first is that anaemia is a disease that should not be underestimated: in pregnant women it is associated with an increased risk of prematurity and perinatal mortality; in children there is convincing evidence of impaired psychomotor development and cognitive performance; and in adults impaired work performance and less efficient response to exercise are well documented (29). In patients in whom anaemia is due t o CD, AGA, or EMA testing may prevent the need for other often useless tests and therapy, since anaemia in CD may easily be corrected by gluten-free diet alone (20). The second reason is that CD may be complicated by intestinal lymphoma, even in the subclinical form that we found in the present study (30,31), and, since strict compliance with gluten-free diet protects against this complication (32), diagnosis and treatment must be as prompt a s possible also for these CD patients with more subtle clinical expressions.…”
Section: G R Corazza Er Almentioning
confidence: 97%
“…These data suggest that the lack of efficacy of oral iron replacement further select conditions related to iron malabsorption, such as untreated CD. Moreover, it has been suggested that iron supplementation therapy may not be required routinely (9,10), as recovery from iron deficiency anemia is believed to occur relatively quickly on a gluten-free diet, even if prospective studies in adults are lacking.…”
Section: Introductionmentioning
confidence: 99%